Phenoloxidase Activity and Fruiting Body Formation in Schizophyllum commune - Leonard, Thomas J. (1971)
Studies of induced haploid fruiting in the Basidiomycete Schizophyllum commune suggested that polyphenoloxidase enzymes may participate in the formation of fruiting bodies. Reported inhibitors of phenoloxidases were found to affect both the activity of these enzymes and the fruiting response. Fertile mycelia were found to give a positive Bavendamm reaction in situ, and cell-free extracts from fertile mycelia exhibited polyphenoloxidase activity when studied spectrophotometrically. Sterile mycelia, on the other hand, were devoid of these activities. Various kinds of mutant homo- and dikaryotic mycelia were studied, and the results suggested a correlation between phenoloxidase activity and fruiting body formation in S. commune.